Serotonin-1A receptor polymorphism (rs6295) associated with thermal pain perception. - Fredrik Lindstedt; Bianka Karshikoff; Martin Schalling; Caroline Olgart Höglund; Martin Ingvar; Mats Lekander; Eva Kosek (PLoS ONE, 2012)
Background Serotonin (5-HT) is highly involved in pain regulation and serotonin-1A (5-HT1A) receptors are important in determining central 5-HT tone. Accordingly, variation in the 5-HT1A receptor gene (HTR1A) may contribute to inter-individual differences in human pain sensitivity. The minor G-allele of the HTR1A single nucleotide polymorphism (SNP) rs6295 attenuates firing of serotonergic neurons and reduces postsynaptic expression of the receptor. Experiments in rodents suggest that 5-HT1A-agonism modulates pain in opposite directions at mild compared to high noxious intensities. Based upon this and several other similar observations, we hypothesized that G-carriers would exhibit a relative hypoalgesia at mild thermal stimuli but tend towards hyperalgesia at higher noxious intensities. Methods Fourty-nine healthy individuals were selectively genotyped for rs6295. Heat- and cold-pain thresholds were assessed along with VAS-ratings of a range of suprathreshold noxious heat intensities (45°C-49°C). Nociceptive-flexion reflex (NFR) thresholds were also assessed. Results Volunteers did not deviate significantly from Hardy-Weinberg equilibrium. G-carriers were less sensitive to threshold-level thermal pain. This relative hypoalgesia was abolished at suprathreshold noxious intensities where G-carriers instead increased their ratings of heat-pain significantly more than C-homozygotes. No differences with regard to NFR-thresholds emerged. Conclusion/significance To the best of our knowledge this is the first study of human pain perception on the basis of variation in HTR1A. The results illustrate the importance of including a range of stimulus intensities in assessments of pain sensitivity. In speculation, we propose that an attenuated serotonergic tone may be related to a 'hypo- to hyperalgesic' response-pattern. The involved mechanisms could be of clinical interest as variation in pain regulation is known to influence the risk of developing pain pathologies. Further investigations are therefore warranted.